A prospective study of serum zinc levels in children presenting with simple febrile seizures - Dr. Sowjan M. (Pediatric Review: International Journal of Pediatric Research, 2019)
Aim: To estimate the levels of serum zinc in children with simple febrile seizures and to compare serum zinc levels between children with febrile seizures and febrile children without seizures.Materials and Methods: A prospective case control study was done on 100 children for a period of one year from June 2018 to January 2019, admitted in Karpaga Vinayaga Institute of Medical Sciences, Padalam, Chennai, who satisfied the inclusion and exclusion criteria. Of these 50 children were diagnosed to have febrile convulsions. The other 50 were febrile children without seizures. Serum zinc levels were measured in all 100 children.Results: Mean Serum zinc levels in children with febrile seizures were 58.4 micrograms/dl and mean serum zinc levels in control group was 94.1 micrograms/dl (p=0.0001). Serum zinc levels were significantly low in children who had febrile seizures of prolonged duration (p=0.0001).Conclusion: These findings revealed that there is correlation between serum zinc and simple febrile seizures. Serum zinc level was significantly lower in children with simple febrile seizures in comparison with febrile children without seizure.